QUALITY OF LIFE OF PATIENTS AFTER SURGICAL TREATMENT OF TRAUMATIC LIMB FRACTURES AT LE VAN THINH HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the quality of life of patients after surgical treatment for traumatic limb fractures at Le Van Thinh Hospital during 2025–2026. Materials and Methods: A prospective longitudinal descriptive study was conducted on 185 patients with limb fractures who underwent surgical fixation at Le Van Thinh Hospital. Quality of life was assessed using the SF-36 questionnaire at two time points: immediately after surgery (T0) and 3 months postoperatively (T3). Results: Traffic accidents were the most common cause of limb fractures, accounting for 53.5% of cases. Plate-and-screw fixation was the most frequently used surgical method (59.7%). At T0, no statistically significant differences in SF-36 scores were observed among groups according to sex, fracture location, age, comorbidities, or surgical methods (p >0.05). After 3 months of follow-up, quality-of-life scores improved significantly in all groups compared with the postoperative period, with statistically significant differences (p
Keywords: upper extremity fracture, lower extremity fracture, quality of life.